GLOBALIZATION OR GLOCALIZATION: A POLITICAL ECONOMY PERSPECTIVE - Noor Fatima; Imran Ashraf, (ASIAN Journal of International Peace & Security (AJIPS), 2020)
Globalization as an economic phenomenon brings not only unfair economic integrations but incompatibility to the diverse culture of the world. All the same, the transformation from globalization to localization brings compatibility to the multi-cultural world by managing the negative consequences of economic globalization. This paper examines the evolution and transformation of the concept of globalization to glocalization. The paper also delineates the history and the development of the concept of glocalization. The paper examines in broad terms concepts, theories, and principles of glocalization. The paper focuses on the epistemological analysis of the globalization and glocalization themes.